Martin McLean, middle school queen - Zaczek, Alyssa (Sterling Children's Books, 2020)
Seventh-grader Martin McLean has trouble expressing himself except at Mathletes competitions and, now, as a female impersonator but his first-ever drag show falls on the same night as an important Mathletes tournament.